Comparison of maternal and neonatal outcome in elective lower segment cesarean section done at 38 and 39 weeks - Sebastian, Gisi; Ghose, Seetesh; Soundararajan, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Time to perform elective LSCS is a relevant issue related to mother and foetus. LSCS can be done from 37 weeks onwards because foetal lungs mature by then. But foetuses born at 37 weeks of gestation have more risk of developing respiratory problems, transient tachypnoea of new born, hypothermia, hypoglycaemia and NICU admission.The purpose of this study is to find out appropriate gestational age at which elective LSCS can be performed without adverse maternal and neonatal outcome. Methods: This is an observational comparative study done on 209 antenatal women who underwent elective caesarean section from December 2014 to January 2016.Patients were divided into two groups after taking consent. Maternal parameters like formation of lower uterine segment need for blood transfusion. Neonatal parameters like Apgar score, respiratory distress syndrome and NICU admission with indication and duration were analyzed by chi-square test. Gestational Age and Pre-Op Hb and Post-Op Hb were analyzed by independent ‘t’test. Results: In this study 55% of the pregnant women belong to 38 weeks,45% belongs to 39 weeks. The formation of lower uterine segment was statistically significant and the need for blood transfusion was slightly increased at 39 weeks. But there was no significant difference in Apgar score, Respiratory distress, NICU admission comparing both study groups. Conclusions: Elective caesarean section can be done safely at 38 weeks without affecting maternal and perinatal outcome.